Numerical simulation of natural convection in a triangular enclosure with caterpillar (C)-curve shape hot wall. (May 2016) - Triveni, Manoj Kr.; Panua, Rajsekhar
Highlights: The problem has been solved in a right-angled triangular cavity for caterpillar (C)-curve shape base hot wall having different width ( w  = 0.20b–0.50b) and aspect ratio ( δ ) with 0.05 ⩽  δ  ⩽ 0.15 and the result is compared with the smooth hot wall. Also, the problem is evaluated for different locations of cold wall and Rayleigh number (1 × 10 5  ⩽ Ra ⩽ 1 × 10 7 ). The heat transfer rate is enhanced for the all locations of cold wall with wavy hot wall, if it is compared with smooth hot wall. The rate of heat transfer is found maximum when both the side and inclined walls are considered as cold wall. The rate of heat transfer is not significantly affected with the variation of width of the curve. The heat transfer rate is increased with the increase of Rayleigh number. Abstract: The present work enlightens the study of laminar natural convection in an isosceles right-angled triangular cavity filled with water. The bottom wall of the cavity contains a caterpillar (C)-curve shape wavy wall, having different width ( w  = 0.20b, 0.25b, 0.33b and 0.50b) and aspect ratio ( δ ) with 0 ⩽  δ  ⩽ 0.15. Vertical and incline walls of the cavity are considered individually and together for cooling purpose. The physical model is solved to examine the effect of constrained parameters such as hot wall profiles, configurations of cold walls and Rayleigh number (10 5 –10 7 ) on the fluid flow and heat transfer. The study is carried out numerically by commercially available software FLUENT 6.3. The deviation in the flow pattern and temperature profile is displayed by streamlines and isotherms contours whereas the variation in heat transfer rate is presented by local and average Nusselt number. It is found from the investigation that the heat transfer rate is enhanced significantly for caterpillar curved shape wavy wall than the flat hot wall. Moreover, the rate of heat transfer is varied profoundly with the location of cold walls.